DNS and BIND - Liu, Cricket (O'Reilly, 2006)
DNS and BIND tells you everything you need to work with one of the Internet's fundamental building blocks: the distributed host information database that's responsible for translating names into addresses, routing mail to its proper destination, and even listing phone numbers with the new ENUM standard. This book brings you up-to-date with the latest changes in this crucial service. The fifth edition covers BIND 9.3.2, the most recent release of the BIND 9 series, as well as BIND 8.4.7. BIND 9.3.2 contains further improvements in security and IPv6 support, and important new features such as i.
Print version record
Keywords: Internet domain names; Internet addresses; Computer network protocols; Distributed databases; Adresses Internet; Protocoles de réseaux d'ordinateurs; Bases de données réparties; COMPUTERS; Networking; Intranets & Extranets; COMPUTERS; Web; General; Kommunikationsprotokoll; Domännamn; Datakommunikation